MODEL PEMBERDAYAAN TATA KELOLA KELOMPOK USAHA KECIL MENENGAH PENGRAJIN BATU PERMATA BUNGUR LAMPUNG SELATAN - Sanusi, Anuar; Wibasuri, Anggalia (IBI Darmajaya, 2015)
Small and Medium Enterprises (SMEs) is a small business from the people who have contributed to economic growth through job creation and multiflier effect. Since 1997, SMEs have become one of the businesses that can save the country from economic crisis. In line with the contribution and economic savior is the government through regulatory policies to encourage SMEs to stabilize the economy. Related to Higher Education policies and service programs to encourage small and medium enterprises then, Sinar Alam one of SMEs engaged in the processing craft gemstone (bungur) managed for generations. This business is located in the village of the district of Tanjung star Srikaton South Lampung Lampung Province. This activity aims to: (1) the empowerment of the community and business partners in order to increase the motivation of entrepreneurs; (2) improve the understanding of the partner business planning and business management; (3) improve the ability of human resources in the production and marketing techniques; and (4) develop entrepreneurial networking Natural Light to support the development of creative economy. The results of this activity are: (1) increasing entrepreneurship group of SMEs; 2) miningkatnya ability groups in business planning (business plan); 3) increasing the ability of a business group Sinar Alam in conducting business operations; 4) increasing network (networking) business cooperation; and 5) business group Sinar Alam models serve as a model entrepreneur development of SMEs groups based society empowerment.Keywords: training, coaching, mentoring, industry, handicrafts